Regulatory overload or incentive deficit? Forty years of structural imbalances in China’s marine environmental policy instruments - Ye, Meng; Guo, Rui (Frontiers in Marine Science, 2025)
China’s marine environmental governance faces a persistent paradox: despite four decades of expanding policy effort and institution building, outcomes have lagged behind expectations. In light of this, we ask whether the core problem lies not in implementation but in a structural imbalance within the policy instrument mix. We develop a Supply–Environment–Demand (SED) framework and apply computational text analysis, combined with framework analysis, to quantify the evolution of, and diagnose structural issues in, marine environmental governance using 57 national-level policies from 1982 to 2024. The findings show that the instrument mix is persistently imbalanced: the Supply, Environment, and Demand functions appear in an approximate ratio of 7:1:1.7, indicating continued Supply-side dominance. Within the Supply function, command-and-control tools—such as bans and penalties—remain foundational, with a recent shift toward planning and zoning. Market-based incentives and property-rights instruments remain underdeveloped and do not scale, while information disclosure on the Demand function expands faster than participatory authority, leaving participation largely procedural. Overall, the system exhibits a structural trilemma—strong supply, anemic environment, and fragmented demand—in which episodic diversification has not produced sustained rebalancing. The governance implication is that policy sequencing and institutional design matter more than adding new instruments. The priority is to embed enforceable ex ante controls and a transparent system for monitoring, reporting, and independent verification through spatial planning, zoning, and legally binding environmental thresholds. On that basis, institutionalize price- and rights-based incentives and enable genuinely empowered public participation so that market signals and social oversight operate effectively at scale. The SED lens thus reframes the implementation gap as a problem of functional allocation and coordination and offers a transferable toolkit for structural rebalancing in coastal jurisdictions.